Flexible Tricolor Flag-liked Microribbons Array with Enhanced Conductive Anisotropy and Multifunctionality - Ma, Qianli (Sci Rep, 2015)
Anisotropically conductive materials are important components in subminiature devices. However, at this stage, some defects have limited practical applications of them, especially low anisotropic degree and high cost. Here, we report novel tricolor flag-liked microribbons array prepared by electrospinning technique. The tricolor flag-liked microribbons array is composed of parallel microribbons, and each microribbon consists of three different regions, just like tricolor flag. The tricolor flag-liked microribbons array is only electrically conductive in the direction parallel to the microribbons, whereas in the perpendicular and thickness directions are insulative. The electrical conductivity along parallel direction reaches up to 8 orders of magnitude higher than that along perpendicular direction. The degree of anisotropy in present study is increased by 2 orders of magnitude than that of the anisotropically conductive material in references reported before. Besides, other functions can be conveniently assembled into tricolor flag-liked microribbons array to realize multifunctionality. Owing to the high electrical anisotropy and multifunctionality, tricolor flag-liked microribbons array will have important applications. Furthermore, a universal technique to prepare microribbons with three functional regions has been established for fabricating excellent multifunctional materials.